Potensi Jasa Lingkungan Penyerap Karbon dan Penyedia Oksigen Hutan Lindung Mangunan, Yogyakarta - Putra, Ghalbi Mahendra; Utama, Pramudya Bagas; Suryatmojo, Hatma; Kusumandari, Ambar Kusumandari (Dampak, 2023)
Forests have multifunction ecology, one of which is environmental services as a CO2 absorber and and O2 producer. The fact is that until now the magnitude of the potential for environmental services as carbon sinks and oxygen producers in the Mangunan Protection Forest is not known, so it is important to research it. The focus of this research is to determine the potential for environmental services in the form of biomass potential, carbon potential, carbon sinks, oxygen providers and their economic value. Carbon data collection in the field by measuring DBH and height of woody vegetation. Calculations using the 2011 BSNI standard and analyzed descriptively. The biomass potential of the Mangunan Protected Forest is 52.83 tons/ha and has threats in the form of trees and fires, so it needs to be preserved. Mangunan Protected Forest Environmental Services in the form of CO2 absorbers of 193.87 tons/ha/year and O2 producers of 141.53 tons/ha/year. The environmental services, if translated properly, are worth Rp. 2,122,640,368. Keywords: environment, sustainability, climate, biomass, vegetation  ABSTRAK Hutan memiliki multifungsi ekologi, salah satunya adalah jasa lingkungan sebagai penyerap CO2 dan penghasil O2. Faktanya sampai saat ini belum diketahui besarnya potensi jasa lingkungan sebagai penyerap karbon dan penghasil oksigen di Hutan Lindung Mangunan, sehingga penting untuk diteliti. Fokus penelitian ini adalah untuk mengetahui potensi jasa lingkungan berupa potensi biomassa, potensi karbon, penyerap karbon, penyedia oksigen dan nilai ekonominya. Pengumpulan data karbon di lapangan dengan mengukur DBH dan tinggi vegetasi berkayu. Perhitungan menggunakan standar BSNI 2011 dan dianalisis secara deskriptif. Potensi biomassa Hutan Lindung Mangunan sebesar 52,83 ton/ha dan memiliki ancaman berupa pohon dan kebakaran sehingga perlu dilestarikan. Jasa Lingkungan Hutan Lindung Mangunan berupa penyerap CO2 sebesar 193,87 ton/ha/tahun dan penghasil O2 sebesar 141,53 ton/ha/tahun. Jasa lingkungan tersebut, jika diterjemahkan dengan baik, bernilai Rp. 2.122.640.368. Kata kunci: lingkungan, kelestarian, iklim, biomassa, vegetasi